2020
DOI: 10.3892/mmr.2020.11408
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA NEAT1 modifies cell proliferation, colony formation, apoptosis, migration and invasion via the miR‑4500/BZW1 axis in ovarian cancer

Abstract: ovarian cancer (oc) is a frequently occurring malignant tumor in women. increasing evidence has indicated that long non-coding rna (lncrna) nuclear paraspeckle assembly transcript 1 (neaT1) participates in oc pathogenesis. Thus, the aim of the present study was to explore the function of neaT1 during oc progression. The expression levels of neaT1, microrna (mir)-4500 and basic leucine zipper and W2 domain-containing protein 1 (BZW1) were assessed via reverse transcription-quantitative Pcr and western blotting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…In addition to the promotion of OC cell proliferation, migration, and invasion, NEAT1 was shown to inhibit OC cell apoptosis by upregulating the expression of basic leucine zipper and W2 domain-containing protein 1 (BZW1) via interaction with miR-4500 [84]. NEAT1 also enhanced EMT of OC cells by upregulating the expression of tight junction protein 3 (TJP3) via interaction with miR-1321 [85].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In addition to the promotion of OC cell proliferation, migration, and invasion, NEAT1 was shown to inhibit OC cell apoptosis by upregulating the expression of basic leucine zipper and W2 domain-containing protein 1 (BZW1) via interaction with miR-4500 [84]. NEAT1 also enhanced EMT of OC cells by upregulating the expression of tight junction protein 3 (TJP3) via interaction with miR-1321 [85].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Another study has also reported the implication of NEAT1 in the tumorigenesis and development of ovarian cancer [ 10 ]. Additionally, NEAT1 knockdown has been reported to suppress ovarian cancer cell proliferation, colony formation, migration, and invasion while stimulating cell apoptosis [ 11 ]. Furthermore, NEAT1 can target microRNA let-7 g-5p (miR let-7 g-5p) and negatively regulate its expression in glioblastoma [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In OC, NEAT1 promotes cancer cell proliferation, invasion, migration, EMT, and angiogenesis by regulating the expression of a wide variety of miRNAs and associated pathways. For example, upregulation of the FGF9 pathway by sponging miR-365 [ 139 ], regulation of TJP3 expression by interacting with and sponging miR-1321 [ 140 ], alteration of cancer proliferation, apoptosis and colony formation by regulation of miR-4500/BZW1 axis [ 141 ], and by sponging many other miRNAs [ 142 ]. Moreover, in a study involving 18 cisplatin-sensitive and 19 cisplatin-resistant OC patients, overexpressed NEAT1 was reported to induce cisplatin resistance ( p = 0.031) in OC cells via the regulation of miR-770-5p and PARP1 [ 143 ].…”
Section: Lncrnas In Female-oriented Cancersmentioning
confidence: 99%